2012
DOI: 10.1007/s00246-012-0465-7
|View full text |Cite
|
Sign up to set email alerts
|

Junctional Ectopic Tachycardia After Congenital Heart Surgery in the Current Surgical Era

Abstract: To determine the incidence of postoperative junctional ectopic tachycardia (JET) in a modern cohort of pediatric patients, evaluate possible risk factors for JET, and examine the effects of JET on postoperative morbidity and mortality. JET is common after congenital heart surgery. JET-related mortality has been a rare event at our center, which is different from previous reports. We reviewed records for pediatric patients who had postoperative arrhythmias between January 2006 and June 2010 at a large tertiary-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 7 publications
4
23
2
2
Order By: Relevance
“…Our JET incidence rate appears lower than the incidence rate of 3% to 10% reported in the literature [1618]. Andreasen et al [17] and Batra et al [18] reported the incidence rate for JET after congenital heart surgery to be 8% and 10%, respectively [16].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Our JET incidence rate appears lower than the incidence rate of 3% to 10% reported in the literature [1618]. Andreasen et al [17] and Batra et al [18] reported the incidence rate for JET after congenital heart surgery to be 8% and 10%, respectively [16].…”
Section: Discussioncontrasting
confidence: 51%
“…Our JET incidence rate appears lower than the incidence rate of 3% to 10% reported in the literature [1618]. Andreasen et al [17] and Batra et al [18] reported the incidence rate for JET after congenital heart surgery to be 8% and 10%, respectively [16]. These studies included lesions such as transposition of great arteries with VSD and Truncus arteriosus, which involve intracardiac repair in the neonatal period.…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, the incidence rate of junctional ectopic tachycardia in group A was 5.7%. This result is in accordance with previous studies, which reported that the incidence rate of junctional ectopic tachycardia after cardiac surgery range from 1.4% to 14.7% 21)22). The relationship between junctional ectopic tachycardia and milrinone use has not been elucidated thus far 23)…”
Section: Discussionsupporting
confidence: 91%
“…36,37,40 In a study by Makhoul et al,239 patients developed arrhythmia in the postoperative period out of the 3850 who underwent congenital heart surgery. 41 In this study, a total of 54 patients developed JET (1.4%), and 11 of the 206 patients that underwent TOF repair (5.3%) had JET. In our study, postoperative JET developed in 13 patients (10.6%), a higher rate than previously reported.…”
Section: Mapca and Early Mortality Or Between Patients That Underwenmentioning
confidence: 98%